Communication-Based Tuberculosis Transmission Prevention in Indigenous Communities in South Nias Regency - Asriwati Amirah; Juliandi Harahap; Khairatunnisa Khairatunnisa; Dian Maya Sari Siregar; Senang Hati Bazikho; Kasrin Purnamasari Gea; Nurul Maharani; Yosi Gloria Br Siahaan; Serfistra Bohalima (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The current Tuberculosis Detection Target in Indonesia for 2024-2025 has not been fully achieved. Many challenges remain to be overcome. Some patients do not complete treatment and discontinue treatment prematurely, which can lead to relapse, further transmission, and the emergence of drug resistance (MDR-TB or XDR-TB). Patients do not understand the importance of completing treatment even though they feel healthy and the dangers of MDR-TB if treatment is discontinued. The Community Service Method used in this community service activity consists of several systematic stages: preparation (Pre-Activity), socialization, interactive lectures, focused discussions or Focus Group Discussions (FGDs), evaluation, and follow-up. The results of this community service activity showed an increase in knowledge, attitudes, and actions in indigenous communities in preventing tuberculosis transmission. It is recommended that health workers always involve community leaders in TB prevention through an active communication approach as traditional leaders serve as role models in decision-making.